Penguatan Kompetensi Guru BK di Mojokerto untuk Mengatasi Perilaku Perundungan Dengan Pelatihan Cognitive Behavior Therapy - Rohmad, Muhammad Ali (Proceedings of Annual Conference on Community Engagement, 2022)
Violence still occurs in schools such as bullying by students against other students. Bullying is an act of individual violence against another individual or group of people against an individual who cannot defend himself either physically or psychologically. Therefore, it takes the efforts of academics from universities to do community service by providing training to teachers, especially BK teachers in the form of cognitive behavior therapy training to prevent bullying behavior. The results of the training show that BK/counseling teachers in Mojokerto feel that they are increasingly mastering cognitive behavior therapy, and know more that the psychological impact of bullying is very dangerous. Furthermore, BK teachers have alternative ways to prevent and overcome bullying behavior, namely cognitive behavior therapy.